2014
DOI: 10.1007/s12035-014-8934-z
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Specific Blockade of Notch Signaling by RBP-J Knockout Attenuates Spinal Cord Injury Accompanied by Compromised Inflammation Response in Mice

Abstract: The outcome of spinal cord injury (SCI) is determined by both neural cell-intrinsic survival pathways and tissue microenvironment-derived signals. Macrophages dominating the inflammatory responses in SCI possess both destructive and reparative potentials, according to their activation status. Notch signaling is involved in both cell survival and macrophage-mediated inflammation, but a comprehensive role of Notch signaling in SCI has been elusive. In this study, we compared the effects of general Notch blockade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…One notion is that infiltrating myeloid cells are polarized and conditioned by cytokines and certain signal pathways. Previous studies in our group showed that Notch signaling is instructive for M1 and suppressive for M2 polarization in microglia, tumor-associated macrophages and macrophages in spinal cord injury 16 22 38 . However, in the current study, with RBP-J deletion, M2 macrophages appear to decrease while M1 type remains in a moderate level.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…One notion is that infiltrating myeloid cells are polarized and conditioned by cytokines and certain signal pathways. Previous studies in our group showed that Notch signaling is instructive for M1 and suppressive for M2 polarization in microglia, tumor-associated macrophages and macrophages in spinal cord injury 16 22 38 . However, in the current study, with RBP-J deletion, M2 macrophages appear to decrease while M1 type remains in a moderate level.…”
Section: Discussionmentioning
confidence: 80%
“…Notch signaling might not only be required for initial macrophage activation, but also participate in polarization at later inflammatory stages. Our group has provided evidence that Notch inhibition by GSI or RBP-J knockout skews macrophage polarization in tumor, hepatic fibrosis and spinal cord injury 16 21 22 . Notch1 signaling-dependent macrophage M2b polarization might play a pivotal role in the pathogenesis of systemic lupus erythematosus 23 .…”
mentioning
confidence: 99%
“…Briefly, to generate myeloid-specific sirt1 −/− mice, mice carrying a floxed sirt1 allele ( Sirt1 flox/flox ; Jackson Laboratory), in which exon 4 of sirt1 was flanked by loxP sites, were crossed with Lyz2-Cre transgenic mice (Jackson Laboratory) ( 33 ). Similarly, to generate myeloid-specific RBP-J −/− mice, mice carrying the Lyz2-Cre transgene were crossed with RBP-J-floxed mice ( RBP-J flox/flox Jackson Laboratory) ( 34 ). Mice were genotyped by performing PCR on tail-derived DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The Notch signaling pathway is known to regulate T and B cell differentiation, activation, and function [45] and neural stem cell (NSC) activation and self-renewal [46]. The effect of Notch signaling on SCI inflammation is not straightforward: globally blocking Notch signaling was found to increase the inflammation cascade, while inhibiting myeloid-specific Notch signaling decreased inflammation, resulting in increased functional outcomes [47]. Extracellular ATP, which is a strong activator of the innate immune system, is increased following SCI and is a major driver of allodynia (experiencing pain from non-painful stimuli) [48].…”
Section: Managing Inflammationmentioning
confidence: 99%